Building Competence Frameworks for Vietnam Middle Management in the Hotel Industry - Do, Vu Phuong Anh (H. : ĐHQGHN, 2019)
Competence frameworks are the trend for human resource management in a dynamic environment. In Vietnam’s dynamic environment, the hotel industry is witnessing fast changes to adapt to the development of the Vietnamese economy. This requires a new model for human resource management in the hotel industry, in particular for middle managers. In this research, the author used a quantitative method to analyze the requirements for competence for middle managers in the hotel industry and has proposed a capability framework, including three main clusters: Professional competence, Executive and management Competence and Self-management competence - for middle managers in the Vietnamese hotel industry